2021
DOI: 10.1002/jbm.a.37214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water‐insoluble hydrophobic polyethylenimines as RNAi vehicles in chronic myeloid leukemia therapy

Abstract: The discovery of RNA interference (RNAi) more than two decades ago opened avenues for avant‐garde cancer treatments that possess the ability to evade issues hampering current chemotherapeutic strategies, owing to its specific gene sequence‐driven mechanism of action. A potent short interfering RNA (siRNA) delivery vehicle designed to overcome physiological barriers is imperative for successful RNAi therapy. For this purpose, this study explored the characteristics and therapeutic efficacy of low‐molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Modified PEI holds significant promise for gene delivery, but selecting the appropriate approach to create successful gene carrier remains a challenge to attain satisfactory therapeutic effects. PEI1.2k is a branched PEI which has been successfully modified with lipids and utilized for both pDNA and siRNA delivery in our lab previously. In this present study, we prepared a library of PEI1.2k-SA-Far polymers (PEI1.2k-SA-Far5, PEI1.2k-SA-Far7, and PEI1.2k-SA-Far9; named as the original mole fraction of SA-Far added to the reaction) from PEI1.2k and SA-Far as described in the experimental section and depicted in Figure a. Due to controlled substitution of hydrophobic SA-Far on hydrophilic PEI1.2k, the resulting lipopolymers prepared here remained water-soluble.…”
Section: Resultsmentioning
confidence: 99%
“…Modified PEI holds significant promise for gene delivery, but selecting the appropriate approach to create successful gene carrier remains a challenge to attain satisfactory therapeutic effects. PEI1.2k is a branched PEI which has been successfully modified with lipids and utilized for both pDNA and siRNA delivery in our lab previously. In this present study, we prepared a library of PEI1.2k-SA-Far polymers (PEI1.2k-SA-Far5, PEI1.2k-SA-Far7, and PEI1.2k-SA-Far9; named as the original mole fraction of SA-Far added to the reaction) from PEI1.2k and SA-Far as described in the experimental section and depicted in Figure a. Due to controlled substitution of hydrophobic SA-Far on hydrophilic PEI1.2k, the resulting lipopolymers prepared here remained water-soluble.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization results revealed that CHO-modified PEI had a significantly smaller size and an enhanced siRNA loading capacity compared with pure PEI. The good therapeutic effect of increased cell uptake was observed in the treatment of chronic myeloid leukemia [ 146 ]. By modifying PEI with tyrosine, Karimov et al were able to significantly enhance the transfection efficiency of siRNA, reduce PEI-induced toxicity, improve biocompatibility, and also show positive therapeutic effects in a mice tumor model.…”
Section: Sirna Nanocarriersmentioning
confidence: 99%
“…One day after treatment with lipopolymer/siFLT3 complexes, cells were seeded in methylcellulose and colonies were counted as described previously (34). The colonies were stained by incubating with the MTT reagent for 2 h, followed by acquiring photographs of individual wells.…”
Section: Colony Formation Assaymentioning
confidence: 99%